Regional disparities in amenities and the life satisfaction of internal migrants - Grace Carolina Guevara-Rosero; Alexander Sarango-Iturralde; Andres García-Suaza (Investigaciones Regionales - Journal of Regional Research)
While migrants pursue better incomes, they might be driven by diﬀerences in amenities between the place of origin and destination. This study aims to determine the eﬀect of diﬀerences in health, educational amenities, and the operational capacity between the place of origin and destination on the life satisfaction of internal migrants. To do so, a generalized ordered logit model is estimated using data from the Survey of Employment, Unemployment and Underemployment of Ecuador for the editions from 2015 to 2017. Our results show that income and amenities are not competing reasons for life satisfaction, they go hand in hand. Diﬀerences in health and educational amenities, as well as variations in the operational capacity of local governments between the places of origin and destination, have an inﬂuence on the life satisfaction of internal migrants. These eﬀects vary depending on the age of the migrant, the size of the city of origin and destination, the reason for migration, and the duration of residence.